Pole-to-pole involvement of varicella zoster virus reactivation following COVID-19 vaccination - Padmamalini Mahendradas; Yash Parmar; Sai Bhakti Mishra; Aditya Patil; Ankush Kawali; Srinivasan Sanjay; Bhujang Shetty (Indian Journal of Ophthalmology, 2023)
The aim of this study is to report the clinical features, imaging findings including confocal imaging, corneal nerve fiber analysis, and management outcomes in a series of three cases of varicella zoster virus (VZV) reactivation following one dose of coronavirus disease 2019 (COVID-19) vaccination. This was a retrospective and observational study. All the patients who developed uveitis post-vaccination were pooled together. Patients who had VZV reactivation were included. Two cases had polymerase chain reaction positive for VZV from aqueous humor. At the time of presentation, IgG and IgM spike protein antibodies for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) were tested. Out of this pool, three patients with classical features to describe pole-to-pole manifestations were chosen. A 36-year-old lady with post-vaccination sclerokeratouveitis associated with reactivation of herpes zoster ophthalmicus, a 56-year-old lady with post-vaccination acute anterior uveitis associated with herpes zoster ophthalmicus, and a 43-year-old gentleman with post-vaccination acute retinal necrosis were included. We present a possible link between anti-SARS-CoV-2 virus vaccination and varicella zoster reactivation in these patients and also describe the clinical features, imaging findings including confocal imaging, corneal nerve fiber analysis, and management with detailed discussion.